Another - Tremblay, Paul (Quill Tree Books, an imprint of HarperCollins Publishers, 2025)
"When Casey Wilson's parents tell him that his friend is coming for a sleepover, he has no idea who that might be. Ever since the Zoom Incident, everyone treats him like a pariah, and his tics are worse than ever. When Morel appears, he's not like any friend Casey has ever met. His skin is like clay, and he doesn't speak. But Casey's parents are charmed by the strange kid, and it's nice to have someone to talk to besides his sister, Ally, who is away at college. As his normally loving parents grow distant from Casey, they gush and fawn over Morel. Casey knows something is wrong -- but with no end in sight to the sleepover, he's exhausted. And in the dark, out of the corner of his eye, Morel doesn't look like a kid at all. . . ."--